Translating the ‘Predictive’ and ‘Hypothetical’ Meanings English-Spanish - Rabadán, Rosa (Meta, 2007)
AbstractThe aim of this article is to explore the different translation options into Spanish for the ‘predictive’ and ‘hypothetical’ English modals. Contrastive analysis and DTS techniques are combined in this corpus-based research. Two monolingual ‘comparable’ corpora are used in order to establish whether and how these meanings are conveyed by forms perceived as being ‘cross-linguistic equivalents.’ A translation corpus contributes evidence to the ‘solutions’ provided to fill in the gaps. The result is an inventory of ‘descriptively correct’ translational options that can be used for different translation applications.